Pilot feasibility study examining a structured self‐management diabetes education programme, DESMOND‐ID, targeting HbA1c in adults with intellectual disabilities. Issue 1 (21st November 2017) - Taggart, L.; Truesdale, M.; Carey, M. E.; Martin‐Stacey, L.; Scott, J.; Bunting, B.; Coates, V.; Brown, M.; Karatzias, T.; Northway, R.; Clarke, J. M.
Abstract: Aim: To report on the outcomes of a pilot feasibility study of a structured self‐management diabetes education programme targeting HbA1c . Methods: We conducted a two‐arm, individually randomized, pilot superiority trial for adults with intellectual disability and Type 2 diabetes mellitus. A total of 66 adults with disabilities across the UK met the eligibility criteria. Of these, 39 agreed to participate and were randomly assigned to either the DESMOND‐ID programme ( n = 19) or a control group ( n = 20). The programme consisted of seven weekly educational sessions. The primary outcome was HbA1c level, and secondary outcomes included BMI, diabetes illness perceptions, severity of diabetes, quality of life, and attendance rates. Results: This study found that the DESMOND‐ID programme was feasible to deliver. With reasonable adjustments, the participants could be recruited successfully, and could provide consent, complete the outcome measures, be randomized to the groups and attend most of the sessions, with minimal loss to follow‐up. The fixed‐effects model, the interaction between occasion (time) and condition, showed statistically significant results (0.05 level) for HbA1c ; however, the CI was large. Conclusion: This is the first published study to adapt and pilot a national structured self‐management diabetes education programme for adults with intellectual disability. This study shows it is possible to identify, recruit, consent and randomize adults with intellectual disabilities to an intervention or control group. Internationally, the results of this pilot are promising, demonstrating that a multi‐session education programme is acceptable and feasible to deliver. Its effectiveness should be further tested in an adequately powered trial. What's new?: No study has previously used a theoretically driven, evidence‐based structured education programme specifically adapted to address diabetes self‐management for adults with intellectual disability and Type 2 diabetes, and their carers. The present pilot study examined the feasibility of a structured education programme, DESMOND‐ID, to improve diabetes self‐management in this population. Although people with intellectual disability have previously been identified as a 'hard‐to‐reach' population, this study shows that it is possible to identify, recruit and obtain consent from adults with a mild to moderate intellectual disability to take part in an intervention study.